2007
DOI: 10.1128/jcm.02178-06
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Strains Isolated from Bloodstream Infections Changed Significantly in 2006

Abstract: Methicillin-resistant S. aureus (MRSA) frequently causes disease outbreaks and has become endemic in many regions, adding to the morbidity, mortality, and cost of care associated with hospital-acquired infections. Enhanced surveillance and infection control measures have been adopted by healthcare institutions (HCIs) to address this unresolved problem (5). In particular, reporting of bloodstream infections (BSI) by MRSA is often mandatory and reduction of BSI rates is a performance target (5,12,21).In the Cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
13
2
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 30 publications
2
13
2
1
Order By: Relevance
“…Since 2000, a prospective, longitudinal survey of BSI has been under way at a regional level in France. Results obtained during the first 7 years of surveillance have been reported (26,27). After sustained and decreasing incidence rates of S. aureus BSI attributed to successful infection control efforts in participating health care institutions (HCIs), we reported in 2006 a sudden increase in incidence that involved two populations of S. aureus strains: one of methicillin-sensitive S. aureus (MSSA) strains and one of MRSA isolates.…”
mentioning
confidence: 93%
See 4 more Smart Citations
“…Since 2000, a prospective, longitudinal survey of BSI has been under way at a regional level in France. Results obtained during the first 7 years of surveillance have been reported (26,27). After sustained and decreasing incidence rates of S. aureus BSI attributed to successful infection control efforts in participating health care institutions (HCIs), we reported in 2006 a sudden increase in incidence that involved two populations of S. aureus strains: one of methicillin-sensitive S. aureus (MSSA) strains and one of MRSA isolates.…”
mentioning
confidence: 93%
“…The survey covered 1,518,475 patient days (PD). The methods, study design, and data for the years 2000 to 2006 have been reported previously (26,27). Briefly, BSI is defined as a positive (not contaminated) blood culture from a patient with clinical or laboratory evidence of infection.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations